39th Winter School on Wave and Quantum Acoustics - Roman BUKOWSKI (Archives of Acoustics)
I have a great pleasure to inform the "AA" Readers that the 39th Winter School on Wave and Quantum Acoustics, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, is planned at the top of March 2010 in beautiful scenery of Silesian Beskidy Mountains. Many times it was organized in Wisła, Skoczów, Szczyrk, and Korbielów, and this year it will be organized again in Szczyrk. As always, the School has been a place where achievements of various sections of physical acoustics (especially molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, acoustoelectronics, photoacoustics, acoustics of solids etc.) are being exchanged. Moreover, some similar and related topics, for example optoelectronics and thermal wave methods, will be presented too. As at previous years the School will be divided on three different, but complementary, parts - Winter Workshops (WW). Chronologically it will be: 6th WW on Acoustoelectronics (chairman Prof. Marian Urbańczyk, Silesian University of Technology, Gliwice), 6th WW on Molecular Acoustics, Relaxation and Calorimetric Methods (chairwoman Dr. Marzena Dzida, Silesian University, Katowice) and 15th WW on Photoacoustics and Thermal Waves Methods (chairman Prof. Jerzy Bodzenta, Silesian University of Technology, Gliwice). Moreover, this year we propose take participation in associated conference - the 4th conference on Integrated Optics - Sensors, Sensing Structures and Methods (chairman Prof. Tadeusz Pustelny, Silesian University of Technology, Gliwice). Many information about these conferences you can find at: http://ogpta.polsl.pl/wswqa and http://ios.polsl.pl After acceptation by revivers the School lectures will be published in one of three journals - in Acta Physica Polonica A, which is published by Polish Academy of Science, in International Journal of Thermophysics published by Springer (only for WW on MARCM and WW on PTWM), or in Journal of Molecular and Quantum Acoustics (annual journal published by Upper Silesian Division of the Polish Acoustical Society). Moreover, all Participants will obtain a last issue of the Journal of Molecular and Quantum Acoustics. Once again we have taken pains to organize this conference taking into account the fact that it is an important event for acousticians, opticians and other Polish and foreign scientists. We hope that this reach conference program will gain acceptance and respect among its potential participants. We count on your numerous response and active participation.